Finding the solution for incomplete small bowel capsule endoscopy - Cotter, José de Almeida Berkeley (2013)
To evaluate whether the use of real time viewer (RTV) and administration of domperidone to patients with delayed gastric passage of the capsule could reduce the rate of incomplete examinations (IE) and improve the diagnostic yield of small bowel capsule endoscopy (SBCE). METHODS: Prospective single center interventional study, from June 2012 to February 2013. Capsule location was systematically checked one hour after ingestion using RTV. If it remained in the stomach, the patient received 10 mg domperidone per os and the location of the capsule was rechecked after 30 min. If the capsule remained in the stomach a second dose of 10 mg of domperidone was administered orally. After another 30 min the position was rechecked and if the capsule remained in the stomach, it was passed into the duodenum by upper gastrointestinal (GI) endoscopy. The rate of IE and diagnostic yield of SBCE were compared with those of examinations performed before the use of RTV or domperidone in our Department (control group, January 2009 - May 2012). RESULTS: Both groups were similar regarding age, sex, indication, inpatient status and surgical history. The control group included 307 patients, with 48 (15.6%) IE. The RTV group included 82 patients, with 3 (3.7%) IE, P = 0.003. In the control group, average gastric time was significantly longer in patients with IE than in patients with complete examination of the small bowel (77 min vs 26 min, P = 0.003). In the RTV group, the capsule remained in the stomach one hour after ingestion in 14/82 patients (17.0%) vs 48/307 (15.6%) in the control group, P = 0.736. Domperidone did not significantly affect small bowel transit time (260 min vs 297 min, P = 0.229). The capsule detected positive findings in 39% of patients in the control group and 49% in the RTV group (P = 0.081). CONCLUSION: The use of RTV and selective administration of domperidone to patients with delayed gastric passage of the capsule significantly reduces incomplete examinations, with no effect on small bowel transit time or diagnostic yield.